Mechanical behavior of magnetorheological dampers after long‐term operation in a cable vibration control system. Issue 1 (19th October 2018) - Wang, Wenxi; Hua, Xugang; Wang, Xiuyong; Wu, Jiali; Sun, Hongxin; Song, Gangbing
Summary: In this paper, 30 magnetorheological (MR) dampers used for vibration control of stay cables after one decade of service were selected to study their long‐term mechanical behavior. The damping capacity of the used MR dampers, including the damping force amplitude and the equivalent damping coefficient, was compared with those of new MR dampers. One used damper still with considerable damping capacity was utilized for the comparative study with a new MR damper under various input voltages, excitation frequencies, and excitation amplitudes. A modified phenomenological mechanical model for used MR dampers was developed based on the experimental observation. Moreover, some used dampers were cut in half, and the remaining volumes of the MR fluid were measured. The iron particles of the MR fluid in the used damper with the worst damping capacity were analyzed using a scanning electron microscopy (SEM). The results show that 24 dampers among the used dampers can still generate considerable damping force. However, the equivalent damping coefficient and the damping force amplitude of these 24 used MR dampers decreased by 32.4% and 29.8%, respectively, on the average. Furthermore, six dampers among the used dampers failed to provide enough damping. The proposed modified mechanical model is more accurate to reflect the mechanical behavior of used MR dampers. It was found that the performance degradation of the used dampers is related to the leakage of the MR fluid and the factor that the surface of MR iron particles became rough and uneven, as observed by the SEM.